Electrophysiological Correlates of Second-Language Syntactic Processes Are Related to Native and Second Language Distance Regardless of Age of Acquisition - Díaz, Begoña; Erdocia, Kepa; de Menezes, Robert F.; Mueller, Jutta L.; Sebastián-Gallés, Núria; Laka, Itziar (Frontiers in Psychology, 2016)
In the present study, we investigate how early and late L2 learners process L2 grammatical traits that are either present or absent in their native language (L1). Thirteen early (AoA = 4 years old) and thirteen late (AoA = 18 years old) Spanish learners of Basque performed a grammatical judgment task on auditory Basque sentences while their event-related brain potentials (ERPs) were recorded. The sentences contained violations of a syntactic property specific to participants’ L2, i.e., ergative case, or violations of a syntactic property present in both of the participants’ languages, i.e., verb agreement. Two forms of verb agreement were tested: subject agreement, found in participants’ L1 and L2, and object agreement, present only in participants’ L2. Behaviorally, early bilinguals were more accurate in the judgment task than late L2 learners. Early bilinguals showed native-like ERPs for verb agreement, which differed from the late learners’ ERP pattern. Nonetheless, approximation to native-likeness was greater for the subject-verb agreement processing, the type of verb-agreement present in participants’ L1, compared to object-verb agreement, the type of verb-agreement present only in participants’ L2. For the ergative argument alignment, unique to L2, the two non-native groups showed similar ERP patterns which did not correspond to the natives’ ERP pattern. We conclude that non-native syntactic processing approximates native processing for early L2 acquisition and high proficiency levels when the syntactic property is common to the L1 and L2. However, syntactic traits that are not present in the L1 do not rely on native-like processing, despite early AoA and high proficiency.